On The Applications of Type II Half Logistic Extended Exponential distribution to Modeling Failure data - Adeniji*, O.E.; Phillips†, S.A.; Ajayi‡, B.; Adeleye§, d N.A. (International Journal of Mathematical Analysis and Modelling, 2023)
This article introduces a three-parameter extension of the Exponentiated exponential distribution called Type II half logistic Extended Exponential distribution. The proposed model is quite flexible and adaptable to model any kind of life-time data. Its probability density function may sometimes be unimodal and its corresponding hazard rate may be of monotone or nonmonotone shape. Standard statistical properties such as it ordinary and incomplete moments, quantile function, moment generating function, reliability function, order statistics, and Renyi entropy are obtained. The maximum likelihood method is used to obtain the estimates of the model parameters. Two practical examples of failure data sets are presented to demonstrate the flexibility of the developed model.